Sustainable Innovations in Apparel Production (Textile Science and Clothing Technology, 2018)
There have been a lot of innovations in making the garment or apparel production sector sustainable. This book highlights sustainable innovations in the apparel production sector, which is the final destination in the textile production segment. Measuring sustainability in clothing is one of the inevitable areas to deal with when it comes to sustainable apparel production, which is also highlighted here.